2020
DOI: 10.3390/diagnostics10110868
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating miR-22-3p and miR-93-5p as Stable Endogenous Control in Tuberculosis Study

Abstract: The diagnosis and prognosis of tuberculosis remains challenging and necessitates the development of a new test that can accurately diagnose and monitor treatment responses. In this regard, miRNA is becoming a potential diagnostic and prognostic biomarker which differentiates treatment respondents from non-respondents for various non-infectious and infectious diseases, including tuberculosis. The concentration of miRNAs varies based on cell type, disease, and site of infection, implicating that selection of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…We guess the reason for this difference is that the situation of HCC patients and the composition of the control group in our study are different from their projects. Korma et al 55 found that miR-22-3p and miR-93-5p are stable reference genes for plasma microRNA analysis in tuberculosis study which is consistent with our results (Figure 4B). Therefore, we predict that miR-22 may become a stable expression reference gene in liver disease research, which needs more data to verify.…”
Section: Discussionsupporting
confidence: 92%
“…We guess the reason for this difference is that the situation of HCC patients and the composition of the control group in our study are different from their projects. Korma et al 55 found that miR-22-3p and miR-93-5p are stable reference genes for plasma microRNA analysis in tuberculosis study which is consistent with our results (Figure 4B). Therefore, we predict that miR-22 may become a stable expression reference gene in liver disease research, which needs more data to verify.…”
Section: Discussionsupporting
confidence: 92%
“…To calculate the miRNA relative fold changes, the ΔΔCt method was used with miR-93 as an endogenous control. This stable internal reference has recently been recommended for human cancer cell lines and plasma samples [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, a total of 11 reference genes ( Figure 7 ) including nine miRNAs, one snRNA, and one piRNA were found in six stains ( Table 2 ). Among them, RF00026 (U6) [ 15 , 50 ], let-7a [ 59 ], let-7i [ 9 ], let-7g [ 9 ], miR-22-3p [ 57 ], miR-26a-5p [ 58 ], and miR-451a [ 9 ] have been reported, and let-7f-5p, let-7b-5p, miR-181a-5p, piR-020829 were newly identified. However, as illustrated in Figure 7 , although there were relatively similar expression profiles between samples of the same fluid or tissue type, samples of different body fluids or tissues did not exhibit consistent expression levels.…”
Section: Resultsmentioning
confidence: 99%